Overcoming Vulnerabilities of Health Care Systems - Pisu, Mauro (OECD Economics Department Working Papers, 2014)
This paper investigates the vulnerabilities of health care systems in OECD and BRIICS countries to adverse secular trends and large macroeconomic shocks. It identifies policies that can ally vulnerabilities considering the institutional setting of health care systems, such as the public-private mix and the main sources of revenues, and the need to balance economic sustainability with the adequacy of services